Participatory approaches in community development projects: An exploratory study of NGOs in northern province - Diluxshana, T.; Nanthagopan, Y.; Thirugnanasampanthar, S. (University of Jaffna, 2020)
This study aims to investigate participatory approaches in community development projects in non-governmental organizations (NGOs). The primary data was obtained from 10 in-depth interviews with 10 NGO project managers in the northern province of Sri Lanka. Thematic analysis was used to identify participatory approaches in community projects. The study revealed that NGOs widely apply participatory approaches in the project initiation, planning, implementation and evaluation stages. Also, the study identified the following practices of participatory approaches in NGOs; Participatory meetings, teamwork, participation in fieldwork, participation in rural and needs assessments, cross-sectional walking, open discussions, community meetings, and participatory evaluation. The project managers emphasized that participatory approaches are very important for the project's success and sustainability in community development projects. However, they emphasized the following obstacles that hinder the effective application of participatory approaches such as political influences, different casts/groups in the communities, lack of technical knowledge among beneficiaries, and conflict between people in the community.
Keywords: Community development projects; Non-governmental organizations and participatory approaches